PENGARUH PERSEPSI RISIKO, PERSEPSI MANFAAT DAN KEPERCAYAAN TERHADAP NIAT PEMBELIAN KONSUMEN DI PORTAL E-COMMERCE ZALORA.CO.ID - Suci Meutia Disa, Teuku Meldi Kesuma (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research aims to ascertain the impact of perceived risk, perceived benefit and trust toward consumer purchase intention. The sample used in this study are the consumer who visited e-commerce portal zalora.co.id. The used research method utilized questionnaires as the research instrument. The amount of questionnaires that had been analyzed were 200 questionnaires. Non probability sampling system had been used for sampling technique. This technique used to the unknown element profitability within the population that was selected as the sample, and the type of used was purposive. Multiple Linear Regression was also used as analysis method to ascertain the impacts from involved variables. The results showed that the independent variables perceived risk, perceived benefit dan trust show the positive influence and significant (sig 0.05) on purchase intention in e-commerce portal zalora.co.id  Key Word: Perceived Risk, Perceived Benefit, Trust, Purchase Intention